2019
DOI: 10.1021/acs.oprd.9b00253
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scalable Synthesis for an Inhaled pan-JAK Inhibitor

Abstract: A scalable synthesis of a pan-JAK inhibitor is described. The original synthesis by the Medicinal Chemistry group has been modified to develop a new protecting group strategy, a 3-step telescoped synthesis to generate an imidazole ring from a nitrile, and a telescoped borylation/Suzuki coupling sequence as well as to replace HATU with process-friendly CDI in the final amidation step. Efficient API purification and polymorph interconversion protocols have been implemented to obtain API with the desired purity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Several more case studies of the successful use of functionalized silicas and resins have been reported by pharmaceutical companies, demonstrating their utility and applicability on an industrial scale. An additional benefit exhibited by functionalized silica scavengers is the ease of metal recovery via incineration. This is a favorable property, as metal catalysts typically account for approximately 5–20% of total manufacturing costs; hence, recovery and potential recycling of the metal are highly beneficial in making the process as economical as possible .…”
Section: Adsorptionmentioning
confidence: 99%
“…Several more case studies of the successful use of functionalized silicas and resins have been reported by pharmaceutical companies, demonstrating their utility and applicability on an industrial scale. An additional benefit exhibited by functionalized silica scavengers is the ease of metal recovery via incineration. This is a favorable property, as metal catalysts typically account for approximately 5–20% of total manufacturing costs; hence, recovery and potential recycling of the metal are highly beneficial in making the process as economical as possible .…”
Section: Adsorptionmentioning
confidence: 99%
“…The yield for 22 was 86% in situ (Scheme 4). Gontcharov and coworkers [14] from Pfizer developed a robust multi-kilogram scale synthetic route for PF-06263276 23 [15]. 23 is an inhaled pan-JAK inhibitor in clinical development for the treatment of chronic obstructive pulmonary disease.…”
Section: Peer Reviewmentioning
confidence: 99%
“…Organics 2022, 3, FOR PEER REVIEW 14 Graham and coworkers [35] from AstraZeneca developed an improved manufacturing route to ceralasertib 71 [13], an ATR inhibitor currently tested as a drug for treating cancer. The new method features an improved Suzuki-Miyaura coupling between 70 and 16 that simplifies the workup and crystallization required by simply performing a solvent swap to 2-methyltetrahydrofuran (2-MeTHF).…”
Section: Scheme 11 Synthesis Of An Intermediate En Route To Lumacaftormentioning
confidence: 99%
“…Gontcharov and coworkers 9 from Pfizer developed a robust multi-kilogram scale synthetic route for PF-06263276 23, 10 an inhaled pan-JAK inhibitor in clinical development for the treatment of chronic obstructive pulmonary disease. A Suzuki-Miyaura coupling is required between an aryl fragment and cyano-substituted indazole to produce a key intermediate for the new synthesis route.…”
Section: Scheme 3 Synthesis Of Azd6738mentioning
confidence: 99%